Biomineralization of calcium carbonates and their engineered applications: a review - Dhami, N.; Reddy, M.; Mukherjee, Abhijit (Frontiers Research Foundation, 2013)
Microbially induced calcium carbonate precipitation (MICCP) is a naturally occurring biological process in which microbes produce inorganic materials as part of their basic metabolic activities. This technology has been widely explored and promising with potential in various technical applications. In the present review, the detailed mechanism of production of calcium carbonate biominerals by ureolytic bacteria has been discussed along with role of bacteria and the sectors where these biominerals are being used. The applications of bacterially produced carbonate biominerals for improving the durability of buildings, remediation of environment (water and soil), sequestration of atmospheric CO2 filler material in rubbers and plastics etc. are discussed. The study also sheds light on benefits of bacterial biominerals over traditional agents and also the issues that lie in the path of successful commercialization of the technology of microbially induced calcium carbonate precipitation from lab to field scale.